2008
DOI: 10.1021/jm800648y
|View full text |Cite
|
Sign up to set email alerts
|

Soluble 3′,6-Substituted Indirubins with Enhanced Selectivity toward Glycogen Synthase Kinase -3 Alter Circadian Period

Abstract: Glycogen synthase kinase -3 (GSK-3) is a key enzyme involved in numerous physiological events and in major diseases, such as Alzheimer's disease, diabetes, cardiac hypertrophy. Indirubins are bisindoles which can be generated from various natural sources or chemically synthesized. While highly potent and selective as GSK-3 inhibitors, most indirubins exhibit low water solubility. To address the issue of solubility we have designed novel analogues of 6-bromo-indirubin-3′-oxime with increased hydrophilicity, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 48 publications
7
98
0
1
Order By: Relevance
“…4A) (16). In line with this, previous studies showed that application of GSK-3␤ inhibitors or its knockdown shortens the period length of cellular rhythms (19,40). Interestingly, Dyrk1a knockdown caused the effect of period shortening of ϳ0.5 h, although it advanced the accumulation timing of nuclear CRY2 as long as 2 to 4 h (Fig.…”
Section: Vol 30 2010supporting
confidence: 78%
“…4A) (16). In line with this, previous studies showed that application of GSK-3␤ inhibitors or its knockdown shortens the period length of cellular rhythms (19,40). Interestingly, Dyrk1a knockdown caused the effect of period shortening of ϳ0.5 h, although it advanced the accumulation timing of nuclear CRY2 as long as 2 to 4 h (Fig.…”
Section: Vol 30 2010supporting
confidence: 78%
“…We screened 5,018 compounds from the Roscoff library including 588 purine derivatives (29) and 400 indirubin derivatives (30,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Their synthesis consists of two successive nucleophilic substitutions on the oxime (134). In a primary step, dibromoethane undergoes a first nucleophilic substitution by attack of the oxime in the presence of Et 3 N to form an intermediate (81).…”
Section: Novel Analogs Of 6biomentioning
confidence: 99%